Contribution of the Kharkiv school of orthopaedic traumatologists to the formation and development of specialized aid to children - Korzh, Mykola; Korolkov, Oleksandr; Golubeva, Inna; Yaremenko, Dmytro; Shevchenko, Stanislav (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
The articled deals with the history of organization and development of orthopaedic-traumatological aid to children in Kharkiv, this aid being given at first by Prof. Fink Yu. Further development of the specialized aid to children was connected with Sytenko Institute of Spine and Joint Pathology, which was founded in 1907 as the Medical-Mechanical Institute. It was here that, for the first time in the country, outpatient reception of children was isolated, children’s orthopaedic department was organized, new methods of conservative and surgical treatment of orthopaedic pathology in children were developed. The article describes achievements of the Institute in treating severe diseases and injuries of the locomotor system in children, as well as the contribution of children’s medical establishments of Kharkiv to the development of the specialized aid to children.